﻿Teachers' views and teaching approaches on the learning of information skills in a Malaysian University - Aidah Abdul Karim ,; ﻿Parilah M. Shah,; ﻿Rosseni Din , (Universiti Kebangsaan Malaysia, 2010)

(untitled)
﻿Using symbolic interactionism perspective, this qualitative study explored perception, teaching approaches, and personal beliefs of universiy teachers in Malaysia on students'learning of informafion skills. Data were collected via observing information skills programs and interviewing the teachers involved in the programs. The findings found that the teachers viewed the student participation in information practices progressively and independently Teachers also perceived several pillars that enabled students to participate in the information practices. Following the perception, teachers employed active and guided learning to help students engage in pillars and components of information practices. The findings are useful for assisting various higher education communities, particularly teachers, librarians, and administrators in Malaysian higher education, to better collaborate in transforming higher education students info knowledge creators and innovators, as required by the national economy and education framework.